Use of home care services among adults with intellectual and developmental disabilities: does where you live matter?. Issue 2 (3rd July 2018) - Martin, Lynn; Ouellette-Kuntz, Hélène; McKenzie, Katherine
ABSTRACT: Home care services are a growing segment of the health care system that support the ageing population in developed nations. In Canada, adults with intellectual and developmental disabilities, living in the community, in a group home, on their own, or with a partner or family, are eligible for home care. This study sought to determine whether (1) home care services received differed based on type of residence, and (2) if, after controlling for other factors, this relationship was modified by geographic region. Secondary analyses of population-level data (2003–2015) were conducted using a cohort of 4456 home care users with developmental disabilities in Ontario (Canada). Logistic regression informed the relationship between residence, region, and home care services used. Home care users with intellectual and developmental disabilities living in group homes were older, had more cognitive and functional impairment, and were more frail. Controlling for these, type of residence was not associated with receiving nursing and therapy services, but it interacted with age and frailty in predicting receipt of meal services. Region modified the effect of residence on receipt of home health aide and homemaking services. Where people live mattered for some but not all services. While similar use of home care services was observed across regions, very different patterns emerged for those living in group homes. Future work is needed to better understand how sectors (home care and developmental and social services) come together to support adults with intellectual and developmental disabilities in the community.